ANALYSIS OF THE EFFECT KNOWLEDGE SHARING, TEAMWORK ON EMPLOYEE ENGAGEMENT AND EMPLOYEE PERFORMANCE IN BARISTAND INDUSTRI SURABAYA THE MINISTRY OF INDUSTRY’S WORK UNIT - Nina Kusumiartono; Ida Aju Brahmasari; I Dewa Ketut Raka Ardiana (Indonesian Journal of Multidisciplinary Science, 2022)
Human resources need to be considered in an organization or agency as a form of business activity. Agencies achieve the target of what they have proclaimed in their agency or company based on their performance. Employee performance can be seen from the data based on the employee performance report (LAKIP) at the Surabaya Industrial Baristand Work Unit of the Ministry of Industry, namely the realization of the agency's performance achievement of 61 which means it does not meet the target number, while the performance achievement should be 71. Human resources can be increased accompanied by culture work based on the average index of professionalism and employee discipline in 2020. Mathew in Gunawan and Wardana (2018 429), wrote that the presence of knowledge sharing in an organization or agency can give birth to innovation and higher performance. Employees are increasingly performing well and productively due to self-motivation, focus, creativity, initiative, communication and good behavior, Bedarkar in Gunawan and Wardana (2018 429). Research purpose from determine effect knowledge sharing, teamwork for employee engagement and employee performance at the Baristard Industry Surabaya, the Ministry of Industry's Work Unit. The research method uses explanatory causality with a sample of 105 respondents. Questionnaires can be used to collect data that can tested using SPSS for validity and reliability. SEM testing using AMOS version 26 can prove is knowledge sharing and teamwork have a significant effect on employee engagement and employee performance.